2013
DOI: 10.3168/jds.2012-5783
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Acute but transient increase in serum insulin reduces messenger RNA expression of hepatic enzymes associated with progesterone catabolism in dairy cows

Abstract: The objective of this experiment was to evaluate the effects of glucose infusion on serum concentrations of glucose, insulin, and progesterone (P4), as well as mRNA expression of hepatic CYP2C19 and CYP3A4 in nonlactating, ovariectomized cows in adequate nutritional status. Eight Gir × Holstein cows were maintained on a low-quality Brachiaria brizantha pasture with reduced forage availability, but they individually received, on average, 3 kg/cow daily (as fed) of a corn-based concentrate from d -28 to 0 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 20 publications
(30 reference statements)
2
9
2
5
Order By: Relevance
“…Previous results from our laboratory have shown that peripheral concentrations of insulin potentially modulates the hepatic metabolism of P 4 (Moriel et al, 2008;Lopes et al, 2009;Vieira et al, 2010Vieira et al, , 2013. Elevated insulin concentrations reduced hepatic expression of P 4 catabolic enzymes P450 2C and P450 3A (Lemley et al, 2008;Vieira et al, 2013), which may further increase circulating concentrations of P 4 (Moriel et al, 2008;Lopes et al, 2009;Vieira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous results from our laboratory have shown that peripheral concentrations of insulin potentially modulates the hepatic metabolism of P 4 (Moriel et al, 2008;Lopes et al, 2009;Vieira et al, 2010Vieira et al, , 2013. Elevated insulin concentrations reduced hepatic expression of P 4 catabolic enzymes P450 2C and P450 3A (Lemley et al, 2008;Vieira et al, 2013), which may further increase circulating concentrations of P 4 (Moriel et al, 2008;Lopes et al, 2009;Vieira et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated insulin concentrations reduced hepatic expression of P 4 catabolic enzymes P450 2C and P450 3A (Lemley et al, 2008;Vieira et al, 2013), which may further increase circulating concentrations of P 4 (Moriel et al, 2008;Lopes et al, 2009;Vieira et al, 2010). Accordingly, Vieira et al (2013) reported that dairy cows in adequate nutritional status receiving jugular glucose infusion (3 h at a rate of 0.5 g/kg of BW) had greater circulating insulin concentrations and reduced hepatic mRNA expression of P 4 catabolic enzymes CYP2C19 and CYP3A4 compared with cohorts receiving saline infusion. Butler et al (2003) observed that hepatic clearance of P 4 is reduced linearly after increasing amounts of insulin infusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of CYP2C19 and CYP3A4 was assessed in samples collected at 0 and 4 h relative to supplementation on d 18, from cows that responded to the estrus synchronization protocol, based on previous research from our group (Vieira et al, 2013).…”
Section: Samplingmentioning
confidence: 99%
“…No presente estudo, no entanto, esse efeito "protetor" não foi relacionado à menor expressão gênica das enzimas que metabolizam a P4 (CYP2C19, CYP3A4, AKR1D1, AKR1C4), visto que não foi encontrada diferença na expressão gênica (Tabela 10), diferente do descrito por Lemley et al (2008). Outros autores também não encontram diferença na expressão gênica dessas enzimas após estímulo com insulina MATTOS, 2012) enquanto que no estudo de Vieira et al (2013) o desafio com insulina diminuiu a expressão das enzimas CYP2C19 e CYP3A4, mas não alterou a P4 circulante.…”
Section: Hormônios E Metabólitosunclassified